Physical activity of children aged 1-4 - Łosień, Tomasz; Mędrak, Anna; Plaskacz, Paweł; Bajerska, Izabela; Reut, Magdalena; Dragon, Emilia; Polko, Martyna; Cebula, Aleksandra (Journal of Education, Health and Sport, 2018)
Introduction: Physical activity plays an important role in the child's development process. The most exposed to the consequences of hypokinesia are children in the period of intensive growth. Movement games during the youngest years have a significant impact on later life, especially on the occurrence of faulty posture or speed of acquiring new motor skills. In the literature, there are reports showing increasing obesity rates among children not only in Poland, but also across the world. It is estimated that this is related to the modern "style" of raising children and the early introduction of electronic toys, tablets, mobile phones and television in order to compensate for the small amount of time devoted to children.The aim of the study: 1) Do parents encourage children to take physical activities? 2) How often do parents spend time with their child in the open air? 3) Is the common creation of games often used in the process of raising a child? 4) Do parents take physical activity with their children? Material and methods: 62 people took part in the study and an original questionnaire consisting of 26 questions was used. The questions included, among other things, the age of the child and parents, the child's physical activity, diet and how they are spendind free time at home. Results and conclusions:72.6% of respondents encourage their children to take regular physical activity. Over half of the respondents said that every day they spend more than an hour with their child in the open air, only 21% create educational games together with their child. Over 72% of children actively participate in the physical activity with parents.